Health technology assessment applied to the selection of a protein module for hospital use (2015)
Introduction: The evaluation of health technologies applied to the selection of a module of protein for hospital use, aims to provide support in choosing products cost effective and safe, in order to facilitate decision making to the different actors involved in the choice of therapeutic alternatives recommended in patients with elevated protein needs, as is the case in this investigation. Aims: To apply a mathematical method - to evaluate multi-protein modules available on the market for institutional nutritional therapy. Methods: Two phases are established, a review of the literature to establish and prioritize technical evaluation criteria of different modules offers protein, and two application of a mathematical model was developed to consider the protein module for use within hospital institutions, which consisted of assigning a value to each of the variables through an established semantic differential scale, which allowed calculating the percentage weight of each of the variables whose sum throw percentage score for each alternative. Results: Regarding the search for technical evaluation criteria for different protein modules deals in the following literature, nature or equivalence conditions of administration and use, safety, and efficacy were identified. Nature is self assessed by rating the chemical amino acid score corrected for protein digestibility (PDCAAS) weighing in assessing 39.05%, referring to the terms of use and management took into account factors included in the distribution systems unit dose with a weight of 27.61%, the efficiency was defined by the protein efficiency ratio (PER) which impacts the 19.53% of the grade and ultimately the safety criterion 13.81% with respect to packaging and labeling. Discussion: There is agreement with that reported in the literature concerning the technical evaluation criteria relevant to the quality of the protein, and the criteria of administration, safety and efficacy. Similarly to conduct triage criteria using the mathematical model in order to consider the protein module for use within hospital facilities, the measure PDCAAS nature, remains the most important when choosing a protein module. However, the total protein content and solubility are similar in all the tested products. Conclusions: When evaluating four alternative protein modules, offered by different pharmaceutical companies, the highest score corresponding to the alternative with a higher rating than 90%, the obtained two alternative protein modules for use in hospitals, which contain whey protein and amino acids in combinations.